How space-number associations may be created in preliterate children: six distinct mechanisms - Nuerk, Hans-Christoph; Patro, Katarzyna; Cress, Ulrike; Schild, Ulrike; Friedrich, Claudia K.; Göbel, Silke M. (Frontiers in Psychology, 2015)
The directionality of space-number association (SNA) is shaped by cultural experiences. It usually follows the culturally dominant reading direction. Smaller numbers are generally associated with the starting side for reading (left side in Western cultures), while larger numbers are associated with the right endpoint side. However, SNAs consistent with cultural reading directions are present before children can actually read and write. Therefore, these SNAs cannot only be shaped by the direction of children’s own reading/writing behavior. We propose six distinct processes - one biological and five cultural/educational - underlying directional space-number associations before formal reading acquisition: (i) Brain lateralization (ii) Monitoring adult reading behavior, (iii) Pretend reading and writing, and rudimentary reading and writing skills, (iv) Dominant attentional directional preferences in a society, not directly related to reading direction, (v) Direct spatial-numerical learning, (vi) Other spatial-directional processes independent of reading direction. In this mini-review, we will differentiate between these processes, elaborate when in development they might emerge, discuss how they may create the space-number associations observed in preliterate children and propose how they can be studied in the future.